THE CORRELATION BETWEEN LANGUAGE LEARNING STRATEGIES AND STUDENTS’ THINKING STYLES AT THE ELEVENTH GRADE OF SMA PLUS BUDI UTOMO MAKASSAR - Kasmiati Kasmiati; Rizka Indahyanti; Endang Ruswiyani (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2025)
This study aims to determine the correlation between language learning strategies and students thinking styles in English learning on students of class XI A SMA Plus Budi Utomo Makassar. Sampling technique used in the study was descriptive research. The population in this research is class XI A in SMA Plus Budi Utomo Makassar. The respondent of this study were 28 students in academic year 2024. Researcher used two questionnaires, the first questionnaire about language learning strategies and the second questionnaire about students thinking styles. Based on the study showed the average value for questionnaire of language learning strategies was 1.143 and the average value of the students thinking styles was 1.087. Based on the result of data processing and analysis, the researcher concluded that English Language Learning Strategy of class XI A at the eleventh grade of SMA Plus Budi Utomo Makassar are Social the total frequency is 35% and Students’ Thinking Style are Form with the total percentage is 31%. The data analysis used in this research was product moment formula which showed that there was there any correlation between English Language Learning Strategy and Students’ Thinking Style there was a significant (variable X) and (variable Y) expressed quit with an average analysis rcount =0.564 while rtable = 0.318. The finding of this research could be synthesized that hypothesis were rcount was higher than rtable. So H1 was accepted and H0 was rejected. Thus, there was a positive significant correlation between language learning and students thinking styles.